1998
DOI: 10.1038/575
|View full text |Cite
|
Sign up to set email alerts
|

Telomere elongation by hnRNP A1 and a derivative that interacts with telomeric repeats and telomerase

Abstract: Telomeric DNA of mammalian chromosomes consists of several kilobase-pairs of tandemly repeated sequences with a terminal 3' overhang in single-stranded form. Maintaining the integrity of these repeats is essential for cell survival; telomere attrition is associated with chromosome instability and cell senescence, whereas stabilization of telomere length correlates with the immortalization of somatic cells. Telomere elongation is carried out by telomerase, an RNA-dependent DNA polymerase which adds single-stran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
231
2
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(245 citation statements)
references
References 32 publications
9
231
2
1
Order By: Relevance
“…In a gel-shift assay using (TTAGGC) [2][3][4] telomeric repeats as probes, we found that 2.5 (TTAGGC) repeats was the minimum for HRP-1 binding. The affinity of HRP-1 binding was markedly higher when we used four (TTAGGC) repeats as a probe, consistent with previous reports that RNP A1 binding to telomeric DNA is length-dependent 9 (Fig. 1c).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…In a gel-shift assay using (TTAGGC) [2][3][4] telomeric repeats as probes, we found that 2.5 (TTAGGC) repeats was the minimum for HRP-1 binding. The affinity of HRP-1 binding was markedly higher when we used four (TTAGGC) repeats as a probe, consistent with previous reports that RNP A1 binding to telomeric DNA is length-dependent 9 (Fig. 1c).…”
supporting
confidence: 92%
“…Gel-shift assays were carried out using purified HRP-1 with the 32 P-end-labeled (TTAGGC) 4 probe in the presence of different amounts of unlabeled (TTAGGC) 4 (lanes 2-6) and nonspecific oligonucleotides (lanes [7][8][9][10][11]. The relative amounts of the competitors added are indicated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Telomerase is composed of telomerase reverse transcriptase (hTERT) [27], telomerase-associated protein (TEP1) [9], and hnRNP A1 [21]. The de novo transcription of the hTERT gene is considered the dominant, rate-limiting step in telomerase activation whereas the expression of hTEP1 and hTR is constitutive [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, hnRNP A1 was shown to bind single-stranded telomeric DNA and telomerase RNA [35]. Depletion of hnRNP A1 expression causes short telomeres and reduces telomerase activity [46,47]. It was postulated that binding of these hnRNPs to telomeres might help in recruiting telomerase to the telomeres.…”
Section: Discussionmentioning
confidence: 99%